Six Poems. (2nd January 2019) - Jiujiu, Hu; Turner, Matt; Weng, Haiying
Abstract : Hu Jiujiu has said that the collection of 100 poems called Fog, from which these poems are taken, was an experiment in resuscitating various images from the Eastern tradition and breathing them into the sundry spiritual crises of modernity. The sequence is illustrative of what he imagined to be a moment in time, where contemporaneity meets a horizon of transcendence. The six selected poems carry the overarching themes of eating, or appetite; sons, or children; movement; journeying; the temple; and introspection.